Sistema de ayuda al diseño de aparatos químicos SADAQ 1.0 - Goya-Valdivia, Abel; Ibarra-Hernández, Vladimir; Gómez-Diez, Rodney; Feitó-Rodríguez, Yudith; Moreno-Rodríguez, Rosendo (Revista Facultad de Ingeniería Universidad de Antioquia, 1998)
(Sin resumen)